A Comparative Study of the Conduction Mechanism in Potassium Halides - Shahi, Kalpana; Kumar, Prahlad (Asian Journal of Chemistry, 2010)
The electrical conduction mechanisms, in direct current and alternating current fields, have been studied using KCl, KBr and KI as samples. Space charge limited conduction and the presence of traps play a major role in direct current measurement. The relaxation effect is predominant in these alkali halides in alternating current fields. Effects of orientational polarization is noted.